POTENSI PANTAI CEMARA, KABUPATEN BANYUWANGI, JAWA TIMUR SEBAGAI KAWASAN EKOWISATA - Agustina Tri Kusuma Dewi; Mega Yuniartik (JFMR (Journal of Fisheries and Marine Research), 2019)
The purpose of this research is to study Cemara Beach, Banyuwangi Regency, East Java in developing responsible and sustainable Ecotourism Areas. The approach used in this study is an analytical descriptive approach with a survey method with sampling on April 7, 2019. From the results of the study, it was found that there are several types of mangrove in Cemara Beach, namely Deruju / Jeruju (Acanthus ilicifolius L), Kambingan (Derris trifoliate), Rhizophora mucronate, and Keranji/ Dadap Laut (Clerodendruminerme) and there are two species of seven species that have protected status, namely Green Turtle (Chelonia mydas) and Lekang Turtle (Lepidochelysolivacea). The minimum NDVI value is -0.53 and the maximum is 0.95 found in the study location. The value of physical and chemical parameters at Cemara Beach also has a good indicator in accordance with the quality standard. The average temperature are 28.8 oC, pH are 5.1, dissolved oxygen are 5.5 mg/ L, and ammonia are 0.07 mg/ L. These parameters are expected to be able to support and provide good indicators in developing the ecotourism sector that trails between turtle conservation areas, mangroves, and tourism.